2013
DOI: 10.4315/0362-028x.jfp-12-232
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Microbial Composition in a High-Throughput Poultry Slaughtering Facility

Abstract: A high-throughput chicken slaughtering facility in Beijing was systematically investigated for numbers of airborne microorganisms. Samples were assessed for counts of aerobic bacteria, Staphylococcus aureus, total coliforms, Escherichia coli, Pseudomonas aeruginosa, Listeria monocytogenes, Bacillus cereus, and Salmonella. During a 4-month period (September to December 2011), samples were collected for 10 min three times daily (preproduction, production, and postproduction). Samples were collected for three con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Our hypothesis and results are also consistent with the results of European studies that have reported Enterobacter, Citrobacter, and Klebsiella as among the most frequently detected Enterobacteriaceae in chicken carcasses at slaughterhouses [Schwaiger et al, 2012]. Several other studies have reported GNOs as airborne microorganisms in poultry slaughter and processing plants [Whyte et al, 2001;Lues et al, 2007;Fallschissel et al, 2010;Liang et al, 2013]. Enterobacteriaceae including resistant P. mirabilis have been reported in European studies as contaminants on retail chicken [Overdevest et al, 2011;Kola et al, 2012].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our hypothesis and results are also consistent with the results of European studies that have reported Enterobacter, Citrobacter, and Klebsiella as among the most frequently detected Enterobacteriaceae in chicken carcasses at slaughterhouses [Schwaiger et al, 2012]. Several other studies have reported GNOs as airborne microorganisms in poultry slaughter and processing plants [Whyte et al, 2001;Lues et al, 2007;Fallschissel et al, 2010;Liang et al, 2013]. Enterobacteriaceae including resistant P. mirabilis have been reported in European studies as contaminants on retail chicken [Overdevest et al, 2011;Kola et al, 2012].…”
Section: Discussionsupporting
confidence: 82%
“…We examined GNO exposures on a relative basis by work area and job duty within this occupational cohort, but our evaluation of exposure is not based on actual sampling of the workplace (which is not possible in the US). Still, other studies examining actual workplaces support our exposure categorization of the workforce in this article [Whyte et al, 2001;Lues et al, 2007;Liang et al, 2013]. The inclusion of a non-worker referent population would improve estimates of the risk of nasal GNO carriage due to exposures from the poultry slaughterhouse environment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation